Decreased vitamin D levels in the pediatric population after COVID-19 lockdown - Paolo Cavarzere; Romina Pausilli; Lara Nicolussi Prinicpe; Rossella Gaudino; Alessandra Guzzo; Gaetano Cantalupo; Franco Antoniazzi (BMC, 2023)
Abstract Backgroud SARS-Cov2 infection began to spread worldwide since December 2019; on March 2020, the World Health Organization characterized its related disease, named COVID-19, as a pandemic. In Italy, to contain the spread of infection a severe lockdown in the spring 2020 was instituted. Other less severe restrictions were imposed in the winter 2020-2021 and in the spring 2021. The containment measures caused a series of consequences for the population and, in particular, for children and adolescents that presented psychophysical problems. The aim of this manuscript is to investigate the serum levels of vitamin D in children and adolescents before, during and after the lockdown consequent to COVID-19 pandemic. Methods This is a retrospective cross-sectional study, including all children and adolescents between 1 to 18 years referring to the Pediatric Endocrinology Service of the University Hospital of Verona, Italy, between January 2019 and December 2021. All patients affected by clinical conditions that involve vitamin D metabolism or assuming vitamin D supplementation were excluded. Results In total, 491 children (36.7% males and 63.3% females) were enrolled in this study. The vitamin D levels decreased over time: 28.3 ± 10.2 ng/mL in 2019; 28.2 ± 11.4 ng/mL in 2020 and 24.9 ± 10.1 ng/mL in 2021 (p < 0.05). The vitamin D levels are significant higher in summer and in autumn in comparison with the levels of winter and spring, regardless of the examined years. Conclusions The measures adopted to contain the COVID-19 pandemic led to a reduction of serum levels of vitamin D in pediatric population, probably due to the reduced solar exposure. This may have severe consequences on the bone metabolism of those children who did not present optimal vitamin D levels even before the lockdown. Therefore, an adequate supplementation of vitamin D is necessary from the end of fall to the beginning of spring (November-April) in all children and adolescents living in Northern Italy.